Association between obesity and behavioral/emotional disorders in primary school-aged children: a cross-sectional study (Faculty of Medicine Universitas Indonesia, 2017)
Background: Obesity in children can increase the risks of various chronic diseases. Mental disorders associated with obesity in children include: depression, anxiety, low self-esteem, hyperkinetic disorders, and increased aggressiveness. This relationship is estimated due to vulnerable genetic expressions in obese individuals. This study aimed to find the association between obesity and behavioral/emotional disorder in primary school-aged children. Methods: This cross-sectional study was conducted on 384 children at Menteng 1 Elementary School, Jakarta from July to September 2015. The study was conducted to find the association between the children’s nutritional status and behavioral/emotional disorders screened by the 17-item Pediatric Symptom Checklist (PSC-17). Chi square analysis was applied in this study. Results: The prevalence of obese children at Menteng 1 Elementary School, Jakarta reached 23.2%, which is higher than Jakarta’s prevalence (14%). 8.7% of the subjects were obese and 13.6% of them were having behavioral/emotional disorders. 20.0% of the obese subjects had behavioral/emotional disorders. The prevalence was higher for internalizing subscale, which was consistent with other studies. Association between obesity and behavioral/emotional disorders was significant for externalizing sub-scale (p=0.036). Externalizing problems caused by obesity might be affected by the social stigma of their peer group. However, obesity in children did not have a statistically significant relationship in internalization sub-scale, attention, and PSC-17 total score (p>0.05). No significant associations towards those sub-scales were thought to be influenced by other factors, playing a role in causing mental disorders in children. Conclusion: In general, obesity was not associated with behavioral and emotional disorders in children, but obesity was related to externalizing behavioral/emotional disorders.